The Urgence of Notary Deed for Organs Transplantation in Framework of Preventing Human Organs Transaction - Muhammad Maulana Kevin Rizaldi; Anis Mahdurohatun; Maryanto Maryanto (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
Trafficking in human organs is a threat and also a crime for humanity. Crimes against humanity, the United Nations then formulated the practice of trafficking in human organs which was carried out with illegal means and purposes as part of a transnational crime. The regulation on organ transplantation in Indonesia is regulated in Act No. 36 of 2009 concerning Organ Transplantation. To ensure legal certainty in organ transplantation, both donors and recipients will submit a written statement not to buy organs from a prospective donor or enter into a special agreement with a prospective donor, which is stated in the form of a notary deed or a written statement ratified by a notary. The research objective is to analyze the urgency of the notarial deed of organ transplantation in the context of preventing the sale and purchase of human organs based on the Minister of Health Regulation No. 38 of 2016, the obstacles that arise in the making of a notary deed, the formulation of a notary deed in the implementation of organ or human tissue transplantation. This research is included in empirical juridical research with descriptive analysis research specifications. Sources of data used are primary data and secondary data. Data collection was carried out by field research and library research, then after the data was analyzed, conclusions were drawn using inductive thinking methods. Based on the results of the study found From the positive law, namely Permenkes No. 38 of 2016 and Islamic law, in organ transplantation it is known that there is a condition that there is no sale and purchase of organs, there is no special agreement that provides benefits to the donor and is carried out with a notarial deed in the form of an agreement or written statement under the hand that legalized or waarmerking. Currently, there are no technical or procedural obstacles in making a notarial deed of organ transplantation in the context of preventing the sale and purchase of human organs. The formulation of a notarial deed in the implementation of human organ or tissue transplants based on the Minister of Health Regulation No. 38 of 2016 is based on the legal arrangement regarding authentic deeds, namely Article 1868 BW.